PENGARUH SERTIFIKASI GURU TERHADAP PENINGKATAN KINERJA GURU DI MTs AL-FALAH JONGGRONG MOJOAGUNG KABUPATEN JOMBANG TAHUN PELAJARAN 2014/2015 - Fatoni, - (Al Tadib : Jurnal Ilmu Pendidikan, 2017)
This study is aimed at finding the influence of teachers certification toward theimprovement of teachers’ performance at MTs Al Falah Jonggrong Mojoagung. As understood thecertification program is the process of granting certificates for professional teachers. The certificatewill be obtained through a series of assessments of teachers held by the Institution of HigherEducation Teaching appointed by the government. In accordance with the Education MinisterRegulation No.18 of 2007, the certification is done by the portfolio. One of the road taken by thegovernment to overcome the low quality of education is to improve the quality of its teachers throughteacher certification. The government hopes that, with disertifkasinya teacher, so that its performancewill increase student achievement increase. The problem of this study is there any influence of teachercertification to the improved performance of teachers in MTs Al-Falah Jonggrong MojoagungJombang in academic year 2014/2015. Data analysis techniques that I use in testing the hypothesis byusing independent t test, considering the results of data analysis can be concluded that: There is theinfluence of teacher certification to the improved performance of teachers in MTs Al-Falah JonggrongMojoagung Jombang in academic year 2014/2015.Keywords: Certification, Performance1 Praktisi